2021
DOI: 10.32832/astonjadro.v10i2.5235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Wood Powder Ash on CBR Value in Stabilized High Plasticity Clay Cement and Lime

Abstract: <p>Cement and lime are widely used as stabilizing agents for soft clays. Some pozzolanic materials have also been used as additives such as asphalt, geosta, fly ash (geopolymer), base ash, salt. Industrial waste such as rice husk ash, coal burning ash (geopolymer) is also used as an alternative for stabilization materials. This research aims to study the effect of sawdust ash, as wood waste, to replace cement and lime on the stabilization of high plasticity clay. The effectiveness of sawdust ash, in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…50% is a high plasticity clay, according to the Atterberg plasticity curve, and the USCS classification with the symbol CH. The swelling potential level of the original soil is in the High category [15].…”
Section: Results and Discussion Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50% is a high plasticity clay, according to the Atterberg plasticity curve, and the USCS classification with the symbol CH. The swelling potential level of the original soil is in the High category [15].…”
Section: Results and Discussion Resultsmentioning
confidence: 99%
“…Subsequent research showed that the results of the mechanical properties test of soil mixed with 6% sawdust revealed that the swelling value reduced by 26.53 percent and the swelling pressure decreased by 47.31 percent the longer the treatment period. The result of the effective treatment period achieved is a treatment period of 4 days, however, because the treatment period is more than 4 days the results tend to be constant [15].…”
Section: Introductionmentioning
confidence: 99%